The pillars of inclusive education for students with ASD: a scoping review based on the case of Spain. - Vidal-Esteve, M. I.; Kossyvaki, L. (International Journal of Developmental Disabilities, 2024)
The inclusion of students with Autism Spectrum Disorder (ASD) has been a complicated, controversial and widely discussed issue amongst the countries of the Western world. The aim of this scoping review is to explore the topic of inclusion of students ASD in Spain as this is illustrated in the international literature. Empirical studies conducted in Spain in the past two decades, which are published in international peer-reviewed journals, were reviewed. Four databases (i.e. Scopus, Wos, PsycInfo and ERIC) were searched for the period 2000–2021 following a set of inclusion criteria and yielded a total of 11 articles to be reviewed. Themes emerging from the review include different types of inclusion, interventions and teaching strategies, teacher training, family-school collaboration, participation of people with ASD in research and gender differences. The discussion focuses on similarities but also differences with relevant publications from both Spain and internationally. The paper closes with implications for practice and ideas for future research.